"Next-Generation" Accountability? Evidence From Three School Districts. (October 2021) - Portz, John
Educational accountability is dominated by a focus on test scores to assess academic achievement. An emerging trend toward "next-generation" accountability includes a broader conception of student learning and multiple metrics. A policy design approach is used to analyze this trend. Four design elements—goals, actors, metrics, and consequences—are used to compare accountability systems in New York City, Los Angeles, and Chicago. Key design trends include broader accountability goals, multiple metrics with different data types, and an emphasis on school improvement. Although facing challenges, urban school districts have opportunities to play a role in shaping this accountability debate.